A novel backstepping adaptive impedance control for an upper limb rehabilitation robot. (December 2019) - Bai, Jing; Song, Aiguo; Wang, Ting; Li, Huijun
Abstract: Stroke contributes to hemiplegia, which severely reduces people's ability to perform activities of daily living. Due to the insufficiency of medical resources, there is an urgent need for home-based rehabilitation robot. In this paper, we design a home-based upper limb rehabilitation robot, based on the principle that three axes intersect at one point. A three-dimensional force sensor is equipped at the end of the manipulator to measure the interaction forces between the affected upper limb and the robot during rehabilitation training. The virtual rehabilitation training environment is designed to improve the enthusiasm of patients. A backstepping adaptive fuzzy based impedance control method is proposed for the home-based upper limb rehabilitation robot to prevent secondary injury of the affected limb. The adaptive law is introduced, and the backstepping adaptive fuzzy based impedance controller is proved in details. Experiments results demonstrate the effectiveness of the proposed control method.